Role of the family physician in the diagnosis and surveillance of progressive supranuclear palsy: a case report - Leite, Sara (2024)
Introduction: Progressive supranuclear palsy (PSP) is a neurodegenerative disease, with a prevalence of 2-7 cases/100,000 individuals. However, these data are likely to be underestimated and many patients remain undiagnosed due to diagnostic challenges. Case description: In December 2018, a 69-year-old woman with hypertension and hypothyroidism went to an open consultation at her family health unit for being sad, tearful, and unwilling to start any activity associated with an anxiety crisis. As depression was suspected, it was decided to start her on sertraline. In January 2019, at a scheduled appointment, her family doctor (FD) noted a poorly fluent speech with psychomotor slowing, which the patient did not recognize as a problem. It was decided to make a referral to neurology after excluding identifiable and reversible causes that would justify the clinical picture. In March, at the neurology consultation, the presence of dysarthria and slightly hyperactive osteotendinous reflexes were noted and interpreted in the probable context of a neuromuscular disease, which was later ruled out by normal electromyography, brain magnetic resonance, and analytical study. In June, executive and writing difficulties were added and the presence of apraxia and frontal dysfunction was highlighted. Because of this, the presence of a neurodegenerative disease was hypothesized and a neuropsychological assessment identified a possible primary progressive aphasia. However, in January 2020, there was an exacerbation of previous symptoms and the presence of occasional unprovoked falls, and a slight limitation of the superior vertical gaze was noted, which was finally associated with the definitive diagnosis of PSP. The patient is currently being followed by her FD for palliative care and psychological support for the patient and her family. Comment: The FD is responsible for the longitudinal continuity of the patient's care, as well as for the management of the disease, which presents in an undifferentiated manner, at an early stage of its natural history, characteristics that place the FD in a privileged position to diagnose, monitor, intervene and refer in situations such as the one presented in this clinical case.